STUDI ARSITEKTUR EPHEMERAL DALAM PEMENUHAN KEBUTUHAN BERHUNI BAGI TUNAWISMA DI JAKARTA BARAT - Michelle Rusli; Diah Anggraini (Jurusan Arsitektur dan Perencanaan, 2023)
Humans will actually continue to look for ways to get a better life. One of them is by moving to a place that feels better and has potential. Big cities are often the target for some people who wander to start a new life, one of them is the city of Jakarta. With all the diversity in Jakarta, this city cannot be separated from the socio-economic problems that are also experienced by various parties, including the marginalized. Marginalized people themselves are people who are marginalized when they fail to achieve a welfare life such as the homeless or commonly called the homeless. The bum comes from the word